Serum metabolomic profiling uncovered metabolic shifts in individuals upon moderate-altitude exposure and identified the potentiality of beta-alanine to ameliorate hyperuricemia - Xuanfu Chen; Guoxiang Zou; Zhibo Yang; Xin Qi; Feier Song; Long Peng; Dingchen Wang; Jingyan Zhou; Jiahui Ma; Haiwei He; Yimei Hong; Yu-E Wang; et al. (Redox Biology)
Background: High-altitude exposure has been associated with an increased risk of hyperuricemia (HU) and gout, though the underlying mechanisms remain poorly understood. Methods: We conducted a comprehensive analysis of the serum metabolome and phenome in both discovery and validation cohorts of Han Chinese individuals who underwent long-term moderate-altitude exposure (∼12 months), as well as in an independent cohort consisting of local Han Chinese and Tibetans residing in Nyingchi (>5 years). Beta-Alanine intervention was applied in hypoxanthine and potassium oxonate-induced in vitro and in vivo experiments. Results: Individuals exposed to moderate altitude exhibited elevated serum urate and an increase in overall medium-chain fatty acids (MCFAs), coupled with a decrease in overall amino acids (AAs) and short-chain fatty acids (SCFAs). Rmcorr correlation analysis revealed a significant negative association between Beta-Alanine and serum urate, whereas nonanoic acid was in versa, potentially driving lower serum urate in long-term exposed residents. Both in vitro and in vivo experiments demonstrated that Beta-Alanine inhibited xanthine oxidase (XOD) and reversed the HU phenotype in human hepatocytes and mice induced by hypoxanthine (HX) and potassium oxonate (PO), with a urate-lowering effect in mice. Hepatic pathology and transcriptome analysis of HU mice treated with Beta-Alanine indicated that the mechanisms involved the inhibition of XOD, amelioration of the inflammation phenotype in hepatocytes, and promotion of renal urate excretion. Furthermore, the 10-fold cross-validation random forest classification (RFC) predictive modeling based on selected metabolites and phenotypes achieved an area under receiver operating characteristic (ROC) curve (AUC) value of 0.93 (95 % confidence interval (CI): 0.85–1.00) and 0.79 (95 % CI: 0.59–0.98) for distinguishing individuals with high risk of asymptomatic HU (AHU) in the training dataset and validation dataset, respectively. Conclusions: This study reveals serum urate and metabolome altered in moderate-altitude exposed individuals and Beta-Alanine intervention could ameliorate hyperuricemia. Our findings suggest that targeting the circulating metabolome may pave novel avenues to counter diseases associated with HU.